Evaluation of the impact of oximeter averaging times on automated FiO2 control in routine NICU care: a randomized cross-over study - Janota, J.; Dornakova, J.; Karadyova, V.; Brabec, R.; Rafl-Huttova, V.; Bachman, T.; Rozanek, M.; Rafl, J. (Frontiers in Pediatrics, 2023)
OBJECTIVE: Changes in oximeter averaging have been noted to affect alarm settings. Automated algorithms (A-FiO2) assess FiO2 faster than oximeter averaging, also potentially impacting their effectiveness. METHODS: In a single NICU routinely using 15 fabian-PRICO A-FiO2 systems, neonates were randomized to sequences of 12 hours among a short (2-4s), medium (10s) and long (16s) oximeter averaging-time, for the duration of their A-FiO2 exposure. Primary endpoints were time in: set target range (dependent on PMA), SpO2 <80%, and SpO2 >98% excluding FiO2=0.21. RESULTS: Ten VLBW neonates were enrolled over 11 months. At entry they were 17 days old (IQR 14-19), with an adjusted gestational age of 29 weeks . The study included 272 days of A-FiO2 (34% short, 32% medium, 34% long). Respiratory support was predominately noninvasive (53% NCPAP, 40% HFNC, 6% NIPPV). The aggregate SpO2 exposures were 67% (IQR 55-82) in the target range, 5.4% (IQR 2.0-10) with SpO2 <80% and 1.2% (IQR 0.4-3.1) with SpO2 >98%. There were no differences in time in the target range among the SpO2 average settings. There were differences at the SpO2 extremes (p≤0.001). The medium and long averaging were both lower than the short, with the difference larger than predicted. Multivariate analysis revealed that these findings were independent of subject, ventilation mode, target range, and overall stability. CONCLUSIONS: This A-FiO2 algorithm is effective regardless of the SpO2 averaging setting. There is an advantage to the longer settings, which suggested an interaction with the controller.